Development of Volleyball Underhand Passing Through Wall Media for Students of MTs Islamiyah Mayang - Pratama, Aidil Gilang; Sari, Liliana Puspa; Helmi, Boby; Usman, Khairul (Educational Sciences Journal, 2025)
This research aims to train students to develop accurate and effective underhand passing skills in volleyball through the use of wall media as a training tool. The study was conducted at MTs Islamiyah Mayang, Bosar Maligas District, Simalungun Regency. The research employed an experimental method with a sample of 15 students. Data analysis techniques included a normality test to assess the effect of wall media training on the accuracy of underhand passing in volleyball. The results based on the pre-test data using passing skill assessments indicated that the majority of students initially demonstrated weak passing performance. The application of wall media exercises showed positive effects in improving students’ underhand passing precision and control.